Genotype–phenotype analysis and functional study of three novel LRP6 variants in non-syndromic oligodontia - Yuan, Yunyun; Zhao, Ya; Meng, Lingqiang; Zheng, Shuyun; Li, Hui; Ren, Jiabao; Li, Beibei; Dou, Chenyun; Hou, Yan; Chen, Wenjing; Zhang, Jing; Ding, Yulin; et al. (Frontiers in Genetics, 2025)
Introduction:Tooth agenesis (TA) is a common craniofacial malformation in humans, characterized by the absence of one or more permanent teeth. Recent studies have identified the low-density lipoprotein receptor-related protein 6 (LRP6) gene as an autosomal dominant contributor to TA. Herein we aimed to identify novel LRP6 variants in patients with non-syndromic oligodontia (NSO) and perform functional analyses of these variants.Methods:Whole-exome sequencing (WES) was conducted on probands and their first-degree relatives to identify potential pathogenic variants. Identified LRP6 variants underwent computational pathogenicity prediction using integrated bioinformatics tools. Subcellular localization patterns were analyzed via immunofluorescence microscopy. Functional characterization of WNT/β-catenin signaling alterations was achieved through Western blot analysis and dual-luciferase reporter assays (TOP-Flash/FOP-Flash systems). Finally, genotype-phenotype correlations in LRP6-associated non-syndromic oligodontia (NSO) were systematically investigated.Results:We identified three novel LRP6 variations (NM_002336): a truncating variant [c.2182C>T (p.Arg728*)] and two missense variants [c.3773C>T (p.Thr1258Met) and c.1441C>T (p.Arg481Cys)]. Immunofluorescence characterization revealed that the missense variants exhibited subcellular localization patterns comparable to wild-type LRP6, with predominant distribution in the plasma membrane and cytoplasmic compartments. Western blot analysis revealed impaired β-catenin expression in cells harboring the LRP6 missense variants, suggesting compromised canonical WNT signaling pathway activity. Functional assessment using the TOP/FOP-Flash luciferase reporter system demonstrated significantly reduced TCF/LEF transcriptional activity associated with these variants, though statistical significance was exclusively observed for the Arg481Cys variant (P < 0.05). Literature review identified 39 LRP6 variants associated with 52 NSO patients, revealing that mandibular second premolars were the most frequently affected teeth, while maxillary first molars were least likely to be affected.Discussion:We identified three novel LRP6 variants in patients with NSO from three Chinese families. Furthermore, we have confirmed through in vitro experiments that these novel LRP6 missense variants lead to impaired activation of the WNT signalling pathway. Finally, we summarized the genotype–phenotype correlation for LRP6-related NSO, finding that LRP6 variants are most likely to affect the mandibular second premolars.